Comparison of time domain simulation methods for ship mooring arrangements - Pengattukunnel Thomas, Basil; Borges, José (My University, 2025)
Safe and effective mooring of ships at berth is a critical aspect of port operations, affecting crew safety and vessel integrity as well as operational cost and efficiency. It has become a common practice to plan ships mooring arrangements in advance using ship dynamics prediction tools. This study employs two prediction tools, one based on a fully nonlinear potential flow method and the other on a semi-empirical method, for simulating the dynamic behaviour of a moored ship in time domain. The simulations are carried out for a barge with a simple geometry, subjected to the primary environmental factors in ship mooring problems, namely wind, current and waves. The isolated and combined effects of these environmental factors on the ship dynamics are investigated by analysing the ship motions as well as mooring lines tensions. Overall, the results obtained from the employed tools were comparable, while the semiempirical method offered substantially faster calculations (lower computational costs) than the potential flow method. However, the study reveals that the lack of suitable models to account for quay wall effects on the moored ship within the semi-empirical method can adversely affect the dynamic behaviour predictions, hence significantly impact the assessment of mooring line arrangement performance.
Keywords: Mooring Line Arrangements; Simulations; Time domain mooring analyses; Potential flow; Semi-empirical model